Decline in Age of Nutritional Rickets, Need for Routine Vitamin D Supplementation in Young Infants - Ammarah Jamal; Hira Raheem; Samar Sajid; Wajeeha Batool (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
Objective: To  determine the age at the diagnosis of rickets in children in a tertiary care hospital of Karachi and to assess the association of age at the diagnosis of rickets with serum levels of vitamin D.  Methods: This cross-sectional descriptive study was carried  out  from  January  2016  to  July  2017  on 240 patients >1 month to 36 months of age, both genders, admitted in the paediatric ward, Civil Hospital, Karachi for various  reasons.  Children  having  clinical  signs  suggestive  of  rickets  were  confirmed to have the disease by radiological evidence, raised serum alkaline phosphatase and reduced serum  vitamin D levels. Children with rickets secondary to chronic  diarrhoea,  non-nutritional  aetiologies  and those taking anticonvulsants, corticosteroids, or vitamin D supplements were excluded from the study.    Data was analysed using SPSS 16 for frequencies of age at the time of diagnosis of rickets and for classification of vitamin D  levels  into  severely  deficient,  deficient,  insufficient  and  normal.  Association of the age at the diagnosis of rickets was  tested  with  serum  levels  of  vitamin  D  by  applying  chi-  square test of independence. Statistical significance was considered at p-value <0.05. Results: Mean age was 6.2 ± 5.9 months. A total of 130 (54.2%) subjects were £6 months of age, in- cluding 84 (35%) £3 months. Serum Vitamin D levels were done in  210  (87.5%)  cases. Total  of  168 (80%) cases were either deficient [141 (67.1%)] or severely deficient [27 (12.9%)] in vitamin D while 42 (20%) had insufficient levels. There was significant association of age at diagnosis of rickets with     serum vitamin D levels. Rickets was an incidental diagnosis in most patients. Conclusion: Nutritional rickets was most common in cases £ 6 months age with a sizable number £3 months. Vitamin D deficiency was the cause in all patients. Significant association was  established  between serum vitamin D levels and age at diagnosis of rickets. Most of the subjects remained unde-   tected until they were investigated on basis of clinical suspicion.